HUMAN CAPITAL MANAGEMENT: PERAN DAN DAMPAKNYA PADA EMPLOYEE BRANDING DI PT. XYZ - Takya Amabel Musa; Suhartini Suhartini; Andriyastuti Suratman (Jurnal Ilmiah Global Education, 2023)
Today, the role of Human Capital Management HCM is very important to make the company business more competitive in the global economic competition. Human capital must retain the top talent employee, beside it must make the employees engage with the company. Providing the best employee value proposition that fits with the company's ability and conditions is the one's element of the company's strategy to make employee engagement. Employees who are engaged will be committed and do more than expected to the company. Employee branding can't be forced but as a willingness and self-awareness that requires emotional link between employee and company. This connection is called an employee engagement. This research attempts to explore the roles and the impacts of HCM in employee branding. The methods used in the research are qualitative with descriptive models The sampling of collecting data is through observation, interview, and questionnaire sent directly to 50 employees as respondents. The results indicate that the Human Capital Management has the roles and impacts to the employee branding directly and undirectly.